Deteksi Cemaran Bakteri Pada Jamu Gendong di Pasar Km 5 Kecamatan Kemuning Kota Palembang - Vivin Pransiska; Ita Emilia; Dewi Novianti; Dian Mutiara; Rangga (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2023)
The manufacture of herbal medicine must pay attention to sanitation and hygiene so that it is free from bacterial contamination. The presence of bacteria that exceeds the threshold set by BPOM RI can have a negative effect on health. This study aimed to analyze the total plate count and Escherichia coli contamination in herbal medicine at KM 5 Market, Kemuning District. This study used a survey method by making direct observations accompanied by sampling at the herbal medicine seller and continued with laboratory examinations. The results showed that the total plate number in herbal medicine gendong 1 was 41.5 x101 colonies/ml which was still below the threshold limit, herbal medicine gendong 2 was 185.5 x 105 colonies/ml and herbal medicine gendong 3 was 21.5 x 105 colonies/ml. above the threshold. Three samples of carrying herbal medicine tested negative for E.coli bacteria.